2022
DOI: 10.1039/d1cy01792f
|View full text |Cite
|
Sign up to set email alerts
|

Efficient metal borate catalysts for oxidative dehydrogenation of propane

Abstract: Boron-based catalysts have attracted attention due to their high selectivity to light olefins in the catalytic oxidative dehydrogenation of propane (ODHP) in the recent years, however, which still faced the...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 56 publications
0
7
0
Order By: Relevance
“…The metal-free B-containing materials, such as h-BN, B 2 O 3 , B substance, and BP, have been reported to exhibit high catalytic performance in the ODHP reaction. Moreover, novel metal borate catalysts such as CoB 4 O 7 and NiB 2 O 6 are synthesized and exhibited remarkable structural stability, which can effectively inhibit boron leaching . In these materials, the second element is used as a frame support to wrap boron atoms, and it can also assist in the formation of oxygenated sites to activate the reaction.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The metal-free B-containing materials, such as h-BN, B 2 O 3 , B substance, and BP, have been reported to exhibit high catalytic performance in the ODHP reaction. Moreover, novel metal borate catalysts such as CoB 4 O 7 and NiB 2 O 6 are synthesized and exhibited remarkable structural stability, which can effectively inhibit boron leaching . In these materials, the second element is used as a frame support to wrap boron atoms, and it can also assist in the formation of oxygenated sites to activate the reaction.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, novel metal borate catalysts such as CoB 4 O 7 and NiB 2 O 6 are synthesized and exhibited remarkable structural stability, which can effectively inhibit boron leaching. 6 In these materials, the second element is used as a frame support to wrap boron atoms, and it can also assist in the formation of oxygenated sites to activate the reaction. Therefore, understanding the role of the second element is expected to benefit the development of novel boron-containing catalysts with improved olefin selectivity.…”
Section: Odhp Mechanism Catalyzed By Bpmentioning
confidence: 99%
See 1 more Smart Citation
“…Herein, we demonstrated that, during the ODH reaction catalyzed by h -BN, the in-situ formed olefins, which were generally considered chemically inert in boron-based catalytic systems 17 , 23 , 24 , played a crucial role in promoting parent alkane conversion and cracking of C-C bonds. The experiments of co-feeding mixture of alkane and olefin together with DFT calculations revealed the synergistic reaction routes of the two kinds of hydrocarbons.…”
Section: Introductionmentioning
confidence: 99%
“…Qian et al investigated efficient metal borate catalysts for oxidative dehydrogenation of propane (ODHP). 31 Two metal borate catalysts (CoB 4 O 7 and Ni 3 B 2 O 6 ) were prepared by a coprecipitation method. Reaction tests showed that both metal borates could catalyze propane dehydrogenation efficiently at 450-540 °C with high selectivity and stability.…”
Section: Introductionmentioning
confidence: 99%